Meiotic studies in Largus rufipennis (Castelnau) (Largidae, Heteroptera). II: reciprocal translocation heterozygosity - Bressa, María José (1998)
Specimens of Largus rufipennis (Castelnau) (Largidae, Heteroptera) from three different populations from Argentina (Itaembe, Misiones Province; Tornquist and Ciudad Universitaria, Buenos Aires Province) were cytogenetically studied. Meiotic characteristics of these populations are compared with previous reports on the species. In the population from Itaembe, heterozygosity for a reciprocal translocation was encountered; this finding is the first report for this type of chromosome rearrangement in the order Heteroptera. The role of reciprocal translocations in karyotype evolution in organisms with holokinetic chromosomes is analyzed and discussed.